Virtue and vulnerability: Discourses on women, gender and climate change - Arora-Jonsson, Seema (Global Environmental Change, 2011)
In the limited literature on gender and climate change, two themes predominate – women as vulnerable or virtuous in relation to the environment. Two viewpoints become obvious: women in the South will be affected more by climate change than men in those countries and that men in the North pollute more than women. The debates are structured in specific ways in the North and the South and the discussion in the article focuses largely on examples from Sweden and India. The article traces the lineage of the arguments to the women, environment and development discussions, examining how they recur in new forms in climate debates. Questioning assumptions about women's vulnerability and virtuousness, it highlights how a focus on women's vulnerability or virtuousness can deflect attention from inequalities in decision-making. By reiterating statements about poor women in the South and the pro-environmental women of the North, these assumptions reinforce North–South biases. Generalizations about women's vulnerability and virtuousness can lead to an increase in women's responsibility without corresponding rewards. There is need to contextualise debates on climate change to enable action and to respond effectively to its adverse effects in particular places.
Keywords: 2000 à aujourd'hui; approches et analyses; discours dominant; environnement; projet charge mentale; périodes historiques; relations nords/suds; ressource en ligne; santé; systèmes d'oppressions; thématiques; vulnérabilité

Luttes XXX : inspirations du mouvement des travailleuses du sexe - Mensah, Maria Nengeh; Toupin, Louise; Thiboutot, Claire (Les éditions du remue-ménage, 2011)
Depuis 1973, des travailleuses et travailleurs du sexe aux quatre coins de la planète se regroupent et se mobilisent. Qui sont ces personnes, comment s’organisent-elles et pourquoi revendiquent-elles la décriminalisation de leur travail? Qu’ont-elles à dire à propos du syndicalisme, du féminisme, de la lutte contre le sida, de la violence ou des phénomènes migratoires? Tout en situant le mouvement des travailleuses du sexe dans son contexte historique et international, cette anthologie unique propose une sélection de documents inédits ou traduits en français pour la première fois. Luttes XXX nous invite à la rencontre d’un mouvement social méconnu. Ici, les voix des travailleuses et travailleurs du sexe, longtemps réduites au silence, s’élèvent, réclament justice.
Keywords: anthologie; approches et analyses; cours; discours dominant; droits des femmes*; fem1000; international; inégalités; justice sociale; mouvements sociaux; premier cycle; santé; systèmes d'oppressions; thématiques; travail; travail du sexe; témoignage